Mistakes in the diagnosis and treatment of atopic dermatitis - Monika Marko; Rafał Pawliczak (Alergologia Polska)
Atopic dermatitis (AD) is defined as a chronic inflammatory dermatosis that is characterized by periods of remission and relapse. Over the last decade, the incidence of AD has increased in industrialized countries, becoming a socio-economic burden because it affects not only patients but also reduces the quality of life of the entire family. Despite the constant expansion and systematization of knowledge, AD is a disease about which many myths circulate. The divergent information concerns primarily the causes and course of AD, as well as diagnosis and therapy. It is easy to make mistakes during the diagnosis and treatment of AD due to the complex clinical picture of the disease and the diversity of phenotypes. Obstacles can also be encountered during differential diagnosis. Because AD mainly affects children, the problem of diagnosis and therapy concerns primarily general practitioners (GPs) and pediatricians. This review aims to identify the most common incorrect decisions made during cooperation with a patient suffering from AD. We emphasized that current diagnostic and therapeutic guidelines are recommended. Therefore, based on European Guideline EuroGuiDerm, we indicate what is inappropriate in treating AD and highlight the most important aspects of this disease management that practitioners should remember. We answer when a mistake may occur in diagnosing AD and what should be remembered when choosing therapy. We also point out that conversation with patients and their caregivers is an element that largely influences the effective treatment of AD.